Teaching Behavior Change Theory in Canada: Establishing Consensus on Behavior Change Theories That Are Recommended to Be Taught to Undergraduate Students in Courses Addressing Health Behavior Change. (March 2021) - Gainforth, Heather L.; Dineen, Tineke E.; Giroux, Emily E.; Forneris, Tanya
There is little guidance on which behavior change theories should be taught in undergraduate courses addressing health behavior change. Delphi consensus methods provide a formal, systematic, and reproducible method for establishing consensus among experts. Objective . Use a Delphi methodology to establish consensus regarding behavior change theories that should be taught to undergraduate students enrolled in health behavior change courses. Method. An online Delphi consensus exercise was completed by instructors who were identified through a systematic search of 94 University course calendars to be teaching health behavior change content to undergraduate students in Canada. In Round 1, 22 participants generated a list of theories taught in undergraduate courses. In Rounds 2 and 3, participants indicated their level of agreement using an 11-point Likert-type scale as to which theories should be taught. Theories that reached predetermined consensus criteria were retained in each round. Results. In Round 1, participants listed over 50 different theories being taught in undergraduate courses. After Round 2, nine theories met consensus criteria which were refined to only six theories in Round 3 (i.e., behavior change wheel, self-determination theory, self-efficacy theory, social ecological model, social cognitive theory, theory of planned behavior). Conclusions . A wide range of theories are taught in undergraduate courses. However, only a minority of these theories reached consensus criteria as being theories that should be taught to undergraduate students enrolled in courses addressing health behavior change. Findings can be used to improve the consistency and quality of instruction of behavior change theories at the undergraduate level.